EFEKTIFITAS PROGRAM PENGAWASAN DAGING DAN TELUR DI UNIT PELAKSANA TEKNIS DAERAH BALAI KESEHATAN HEWAN DAN MASYARAKAT PROVINSI SULAWESI - RONDONUWU, RAFLI; TAMPI, GUSTAAF; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2021)
This research aims to determine the effectiveness of the Meat and Egg Control Services in the RegionalTechnical Implementation Unit of the Animal and Community Health Center of North Sulawesi Province.This study uses a qualitative method. The techniques used in data collection in this study were interviews,observation and documentation. After the data was collected, the data were analyzed qualitatively with adescriptive narrative supported by primary and secondary data. The results of this study indicate that, theeffectiveness of services carried out by the UPTD Center for Animal and Community Health of NorthSulawesi Province has been running well, but the obstacles faced are limited experts and insufficientbudget.Keywords: Service Effectiveness, Supervision, UPTD, Laboratory